Physical Activity and Sleep/Wake Behavior, Anthropometric, and Metabolic Profile in Pediatric Narcolepsy Type 1 - Filardi, Marco; Pizza, Fabio; Antelmi, Elena; Pillastrini, Paolo; Natale, Vincenzo; Plazzi, Giuseppe (Frontiers in Neurology, 2018)
Objectives: Regular physical activity is routinely recommended in children and adolescents suffering from narcolepsy type 1 (NT1), but controlled studies analyzing its influence on sleep/wake behavior, metabolic, and anthropometric profile in pediatric NT1 are lacking. Methods: Fifty consecutive drug-naïve NT1 children and adolescents were assessed through actigraphic, clinical, and metabolic evaluations. Patients were compared with respect to their engagement in leisure-time physical activities (LTPA): patients engaged in LTPA (n = 30) and patients not engaged (No-LTPA, n = 20), respectively. Results: LTPA patients presented lower BMI, with different BMI categories distribution and higher HDL cholesterol, when compared with No-LTPA subjects. Increased night-sleep duration, higher sleep quality, and reduction of nap frequency were documented through actigraphy in LTPA subjects. Subjective sleepiness, as measured by ESS-CHAD, was also lower in LTPA subjects while cataplexy frequency proved similar between the two groups. Discussion: In pediatric NT1 patients, regular engagement in LTPA is associated with significant differences on sleepiness, anthropometric and metabolic profile and objectively assessed sleep/wake behavior. Engagement in LTPA is beneficial and should be strongly encouraged in pediatric NT1 patients.